2013
DOI: 10.1166/jnn.2013.7376
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Magnetic Fe<SUB>3</SUB>O<SUB>4</SUB>/SiO<SUB>2</SUB> Core–Shell Nanorods for the Removal of Arsenic

Abstract: A novel magnetic Fe3O4 core-shell nanorods (MCSNs) were synthesized by crosslinking amine functionalized Fe3O4@SiO2 core-shell nanoparticles with 1,2-bromochloroethane. These nanorods were then protonated with dilute HCl. The MCSNs nanorods were characterized using FT-IR, N2 adsorption, VSM, SEM and TEM. The surface area of MCSNs nanorods was found to be 335 m2/g, which is higher than bare iron oxide and amine functionalized Fe3O4@SiO2. These nanorods were used simultaneously as ion-exchanger and adsorbent for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…During the last decade, growing interest has been evoked in the application of iron oxides in industry and environmental processes, [1][2][3][4][5][6] especially for the transition metal substituted magnetites as catalysts with nano-size. [7][8][9][10][11][12][13][14] One of the most promising applications should be as heterogeneous Fenton catalysts in the degradation of organic pollutants, e.g., dyes, phenol and hydroquinone, [15][16][17][18] due to the merits of easy handling, low cost, nontoxicity and environmental harmony.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, growing interest has been evoked in the application of iron oxides in industry and environmental processes, [1][2][3][4][5][6] especially for the transition metal substituted magnetites as catalysts with nano-size. [7][8][9][10][11][12][13][14] One of the most promising applications should be as heterogeneous Fenton catalysts in the degradation of organic pollutants, e.g., dyes, phenol and hydroquinone, [15][16][17][18] due to the merits of easy handling, low cost, nontoxicity and environmental harmony.…”
Section: Introductionmentioning
confidence: 99%
“…Babu et al reported that the adsorbed arsenic on magnetic Fe 3 O 4 core-shell nanorods was easily removed by magnetic separation and regenerated by acid treatment, resulting in an arsenic removal rate of more than 99% [29]. Feng et al synthesized superparamagnetic acid-coated Fe 3 O 4 nanoparticles with a high specific surface area through an environmentally friendly hydrothermal route, which exhibited a maximum adsorption capacity of 16.56 mg/g for arsenic(V) and 46.06 mg/g for arsenic(III) [61].…”
Section: Iron Oxidesmentioning
confidence: 99%
“…Note that the initial As ion concentrations are normally very low in practical applications; hence the capacity to remove As ions at low concentrations is a better criterion for selecting a suitable metal oxide adsorbent [18][19][20]. Moreover, the development of nanomaterials [9], especially those with heterogeneous structures, such as porous materials [21][22][23][24], spheres [25][26][27][28][29][30][31], hierarchical materials [32][33][34][35][36], nanocomposites [37,38], nanoparticles [39,40], nanosheets [41][42][43][44], nanojunctions [45], nanowires [46,47], nanoflowers [48], and binary metal oxides [49,50], is expected to play a key role for the diversified applications, including the detection and remediation of water pollution. The design and application of novel nanostructured metal oxides has received more and more attention in the purification of arsenic contaminated water in the past few decades.…”
Section: Introductionmentioning
confidence: 99%
“…5 MNCs with requirements mentioned above are popular in the fields such as drug delivery, 6-8 enrichment or separation of proteins, 9,10 magnetic resonance imaging [11][12][13] and wastewater purification or melamine detecting. [14][15][16] Silica-coated iron oxides, Fe 3 O 4 -SiO 2 , are typical MNCs that have been applied in many fields due to their unique physical and chemical properties. [17][18][19][20][21][22][23] The inner nanosized Fe 3 O 4 core possesses magnetic properties, and the outer shell of silica protects the inner magnetite core and provides sites for surface functionalization.…”
mentioning
confidence: 99%
“…Also, the uniform coating of magnetic nanoparticles on the one dimensional template is essential for the controlling of orientation. Although some researchers had reported one dimensional MNCs, 15,17,25,26 the controlling of orientation for MNCs was not involved. Therefore, we developed a method of synthesizing one dimensional MNCs, whose orientation could be controlled by external magnetic field.…”
mentioning
confidence: 99%